Evaluation of irisin as a novel biomarker for early diagnosis of neonatal sepsis: A prospective case-control study - Doğan, Selçuk; Aydin, Mustafa; Aydin, Süleyman; Taşkin, Erdal (Kare Publishing, 2025)
Objective: Neonatal sepsis is a life-threatening condition characterized by systemic infection during the first 28 days of life. Early and accurate diagnosis is critical to reducing morbidity and mortality. Irisin (IRI), a recently identified protein with anti-inflammatory and cytokine-like properties, has been suggested as a potential biomarker for various inflammatory conditions. However, its role in neonatal sepsis remains unexplored. This study aimed to evaluate the potential of irisin as a novel biomarker for the early diagnosis of neonatal sepsis in a prospective case-control design. Material and Methods: This study included 58 neonates (30 with sepsis and 28 healthy controls) admitted to the neonatal intensive care unit. Neonates in the sepsis group were diagnosed based on clinical criteria, elevated sepsis scores, and laboratory markers, while controls were healthy neonates without infectious risks. Results: IRI levels were significantly lower in the sepsis group compared to the control group (p<0.01). A negative correlation was observed between IRI and CRP levels (r=-0.378, p<0.05), while no significant correlation was found between IRI and white blood cell count. ROC analysis revealed that irisin had an AUC of 0.843, with a sensitivity of 93% and specificity of 68% at a cutoff value of 10.48 ng/mL. Conclusion: This study demonstrates that irisin levels are reduced in neonatal sepsis and exhibit a significant inverse correlation with CRP. These findings suggest that irisin could serve as a promising biomarker for the early diagnosis of neonatal sepsis. © (2025), (Kare Publishing). All Rights Reserved.
Keywords: Biomarkers; C-reactive protein (CRP); early diagnosis; irisin; neonatal sepsis